2022
DOI: 10.1007/s42161-022-01223-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of additional fire blight resistance candidate genes following MinION Oxford Nanopore sequencing and assembly of BAC clone spanning the Malus fusca resistance locus

Abstract: Pyramiding different fire blight resistance genes and QTLs in future apple cultivars is the most eco-friendly way to combat this disease. Identification of strong fire blight resistance donors, and introgression of their resistance into apple breeding material are a continuing effort of breeding programs. Thus, enormous effort is been put into breeding research to understand host – pathogen interactions and mechanisms of resistance found in Malus. The crabapple Malus fusca (accession MAL0045) is highly resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
4
5
0
Order By: Relevance
“…are not products of coevolution with the Erwinia due to their lack of positioning within clusters of paralogs (i.e., arrays). However, the results presented by Emeriewen et al (2022) and our genome support a co-evolutionary origin of the fire blight resistance in M. fusca. Our assembly demonstrates that the Emeriewen et al (2022) candidate R-gene was located within a tandem array of similar R-genes, which also span into other Malus spp.…”
Section: Comparing Apples To Apples: Synteny Within Malussupporting
confidence: 48%
See 2 more Smart Citations
“…are not products of coevolution with the Erwinia due to their lack of positioning within clusters of paralogs (i.e., arrays). However, the results presented by Emeriewen et al (2022) and our genome support a co-evolutionary origin of the fire blight resistance in M. fusca. Our assembly demonstrates that the Emeriewen et al (2022) candidate R-gene was located within a tandem array of similar R-genes, which also span into other Malus spp.…”
Section: Comparing Apples To Apples: Synteny Within Malussupporting
confidence: 48%
“…However, the results presented by Emeriewen et al (2022) and our genome support a co-evolutionary origin of the fire blight resistance in M. fusca. Our assembly demonstrates that the Emeriewen et al (2022) candidate R-gene was located within a tandem array of similar R-genes, which also span into other Malus spp. and domesticated cultivars.…”
Section: Comparing Apples To Apples: Synteny Within Malussupporting
confidence: 48%
See 1 more Smart Citation
“…are not products of coevolution with the Erwinia due to their lack of positioning within clusters of paralogs (i.e., arrays). However, the results presented by Emeriewen et al, (2022) and our genome support a co-evolutionary origin of the fire blight resistance in M. fusca. Our assembly demonstrates that the Emeriewen et al, (2022) candidate R-gene was located within a tandem array of similar Rgenes, which also span into other Malus spp.…”
Section: Resolving the Fire Blight Resistance Locus (Fb_mfu10)supporting
confidence: 48%
“…Within the fine-mapped boundaries identified by Emeriewen et al, (2018) we identified several genes including a tandem duplication array consisting of four copies ( MfusH1_10g02031, MfusH1_10g02036, MfusH1_10g02040, and MfusH1_10g02042 ) of the G-type lectin S-receptor-like serine/threonine-protein kinase genes implicated by Emeriewen et al, (2018;2022). Since similar resistance receptors ( i.e., R-genes) are often part of such tandem duplications; we hypothesized that apart from sequence polymorphism, copy number variation (CNV) within this locus could potentially contribute to the resistance phenotype.…”
Section: Resultsmentioning
confidence: 84%